ТЕОРЕТИКО-МЕТОДИЧНІ ОСНОВИ ВИБОРУ СТРАТЕГІЇ ІННОВАЦІЙНОЇ АКТИВНОСТІ ПЕРСОНАЛУ - Ястремська О. М.; Волкова Л. О. (World Science, 2019)
The theoretical and methodological aspects of strategic management of innovative activity of the personnel are investigated. The classification of strategies of innovative activity of the personnel is offered. The characteristics and methodological approaches of substantiation of managerial decisions at the choice of strategy and its implementation are specified. Ways to motivate employees to participate in innovative development are identified. Integrated use of methods of stimulating innovative work is envisaged. The suggestions presented in the article can be the basis for solving the tasks of developing optimal actions to stimulate innovative activity of staff and increase the efficiency of the innovation process.